Whole-Transcriptome Analysis of Preadipocyte and Adipocyte and Construction of Regulatory Networks to Investigate Lipid Metabolism in Sheep - Xiao, Cheng; Wei, Tian; Liu, Li Xiang; Liu, Jian Qiang; Wang, Chun Xin; Yuan, Zhi Yu; Ma, Hui Hai; Jin, Hai Guo; Zhang, Li Chun; Cao, Yang (Frontiers in Genetics, 2021)
Many local sheep breeds in China have poor meat quality. Increasing intramuscular fat (IMF) content can significantly improve the quality of mutton. However, the molecular mechanisms of intramuscular adipocyte formation and differentiation remain unclear. This study compared differences between preadipocytes and mature adipocytes by whole-transcriptome sequencing and constructed systematically regulatory networks according to the relationship predicted among the differentially expressed RNAs (DERs). Sequencing results showed that in this process, there were 1,196, 754, 100, and 17 differentially expressed messenger RNAs (mRNAs), long non-coding RNAs (lncRNAs), microRNAs (miRNAs), and circular RNAs (circRNAs), respectively. Gene Ontology analysis showed that most DERs enriched in Cell Part, Cellular Process, Biological Regulation, and Binding terms. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis found that the DERs primarily focused on Focal adhesion, phosphoinositide 3-kinase (PI3K)-Akt, mitogen-activated protein kinase (MAPK), peroxisome proliferator-activated receptor (PPAR) signaling pathways. Forty (40) DERs were randomly selected from the core regulatory network to verify the accuracy of the sequence data. The results of qPCR showed that the DER expression trend was consistent with sequence data. Four novel promising candidate miRNAs (miR-336, miR-422, miR-578, and miR-722) played crucial roles in adipocyte differentiation, and they also participated in multiple and important regulatory networks. We verified the expression pattern of the miRNAs and related pathways’ members at five time points in the adipocyte differentiation process (0, 2, 4, 6, 8, 10 days) by qPCR, including miR-336/ACSL4/LncRNA-MSTRG71379/circRNA0002331, miR-422/FOXO4/LncRNA-MSTRG54995/circRNA0000520, miR-578/IGF1/LncRNA-MSTRG102235/circRNA0002971, and miR-722/PDK4/LncRNA-MSTRG107440/circ RNA0002909. In this study, our data provided plenty of valuable candidate DERs and regulatory networks for researching the molecular mechanisms of sheep adipocyte differentiation and will assist studies in improving the IMF.